Geçmişi Geleceğe Aktarmak: Kültürel Miras Alanında Dijital İkiz Oluşturma. - Yıldırım Altun, Cemile (Electronic Turkish Studies)
Digital twin technology represents a groundbreaking approach in the conservation, management, and sustainable conservation of cultural heritage. By generating high-fidelity digital replicas of cultural properties, this technology facilitates detailed analyses of historical structures, archaeological sites, and works of art. Data acquired through techniques such as laser scanning, photogrammetry, geophysical imaging, and unmanned aerial vehicles (UAVs) are processed using three-dimensional (3D) modeling and artificial intelligence (AI)-assisted analysis. This enables the monitoring of structural changes over time and allows for the systematic planning of restoration processes. Digital twins play a crucial role in documentation, conservation, and restoration efforts, while also enabling the simulation of environmental and natural disaster impacts on heritage structures, thereby supporting the development of proactive conservation strategies. Furthermore, the integration of virtual and augmented reality technologies enhances public engagement and awareness by providing immersive cultural heritage experiences. The primary advantages of digital twin technology include real-time structural monitoring, damage assessment, and the evaluation of material deterioration. These processes can be digitally simulated prior to physical interventions, optimizing both cost and time efficiency. Moreover, digital twin models facilitate interdisciplinary collaboration by enabling seamless data sharing among researchers, conservation specialists, and heritage managers. However, several challenges must be addressed, including the management of large-scale datasets, the requirement for specialized technical expertise, and financial sustainability. The storage and processing of high-resolution digital models necessitate robust data management infrastructures. Additionally, the effective application of digital twin technology depends on the availability of professionals with interdisciplinary expertise in engineering, heritage science, and computational methodologies. Future advancements in this domain will likely be driven by the integration of artificial intelligence and machine learning for enhanced analytical capabilities, the expansion of cloud-based data management systems, and the development of specialized training programs for cultural heritage professionals. Strengthening collaborations among disciplines such as engineering, archaeology, art history, and computer science will further enhance the efficacy of digital twin applications in cultural heritage conservation. In conclusion, digital twins offer a transformative approach to the conservation and management of cultural heritage, ensuring the sustainable transmission of historical structures to future generations. However, to maximize their potential, significant efforts are required to enhance technical infrastructure, improve data governance strategies, and foster capacity-building initiatives. This study critically examines the role of digital twins in cultural heritage conservation, highlighting existing challenges and exploring future opportunities while proposing strategic frameworks for their effective implementation.